LEGAL ANALYSIS OF THE CRIMINAL JUSTICE SYSTEM IN HANDLING DRUG ABUSE CRIMES COMMITTED BY CHILDREN IN SURABAYA - Arcy Pratama, Praditya; Soeprijanto, Troeboes; Nugraheni, Nadea Lathifah (Jurnal Meta-Yuridis, 2024)
Narcotics abuse by children is a behavioral deviation or unlawful act. The increase in narcotics abuse among the younger generation is very dangerous for the nation's future generations who do not yet have legal protection against perpetrators and victims of narcotics abuse who are still minors. The aim of this research is to determine the form of criminal responsibility for children who commit criminal acts of narcotics abuse and how to analyze the criminal justice system in handling cases of criminal acts of narcotics abuse committed by children based on decision no. 9/PID.SUS-Anak/2021/PT SBY. The method used is the normative legal method which places the law as a building of a system of norms, the norm system refers to the principles, norms, rules of statutory regulations, court decisions, agreements and doctrines, often conceptualized as what is written in the regulations. Legislation or law is conceptualized as a rule or norm which is a benchmark for human behavior. Based on the results of the analysis, it is known that the criminal responsibility of children who use narcotics has been regulated in Law Number 35 of 2009 concerning Narcotics. Based on the a quo regulations, the child will be rehabilitated. In this case, rehabilitation is divided into 2 types, namely medical rehabilitation and social rehabilitation. Rehabilitation efforts for children who use narcotics should be supported by all groups. Bearing in mind that rehabilitation efforts are more oriented towards the goal of recovering from undesirable conditions and can also guarantee children's rights. Children who abuse narcotics can be subject to sanctions in the form of actions and criminal penalties. Children as victims of narcotics abuse also receive protection from the state and government institutions.